Analysis of potential hydration opportunities during future football tournaments based on data from the 2018 FIFA World Cup - Wardenaar, F. C.; Beaumont, J. S.; Boeckmann, J.; van Geffen, B.; Vanos, J. K. (Science and Medicine in Football, 2024)
The World Cup is traditionally held oppressive thermal conditions. Therefore, teams should follow heat strain mitigation strategies, including optimal fluid ingestion. The objective of this analysis was to assess and visually communicate match-based World Cup player hydration opportunities and behaviors. Broadcast recordings of the 2018 World Cup (June-July) were analyzed. Descriptive data were reported for match duration, the number, type, and duration of breaks, and player-initiated hydration moments, as well as environmental conditions categorized as `no thermal stress` and `thermal heat stress.` The median number and interquartile range of total match breaks were 7 [5-8] during official breaks, with a duration of 42 [23-72] seconds. There were 2 [1-3] player-initiated hydration moments per game, with a duration of 77 [55-100] seconds. On top of the 29% (#126) of breaks in which drinking occurred, an additional 26% (#33) of self-initiated drinking was registered with a duration of 7 [4-28] seconds without an official break. There was no significant difference (P = 0.22) in self-initiated hydration between thermal conditions. Relative percentages showed suboptimal use of substitution (14%) and VAR (38%) breaks vs. injury breaks (75%). In conclusion, football players did not sufficiently use available breaks to hydrate.